The role of lipid profile as an early indicator of preeclampsia - Jeevika Gupta; Monica Soni; Harsha Charaya; Asmita Nayak (Journal of Current Research in Scientific Medicine, 2022)
Background: Preeclampsia is called the “disease of theories” because its direct cause is still debated. Among all maternal deaths worldwide, 19% of deaths are due to hypertension during pregnancy (World Health Organization 2014). Early diagnosis and management remain the cornerstone in the management of preeclampsia. Estimation of serum lipid profile early in pregnancy could help to identify high-risk cases prone to preeclampsia, thereby reducing morbidity and mortality associated with preeclampsia. The study aimed to determine the role of serum lipid profile in the early prediction of preeclampsia. Methodology: This was a hospital-based prospective study done among pregnant women with a period of gestation of 20 ± 1 week enrolled after screening for inclusion and exclusion criteria and informed consent and institutional ethical committee approval, samples for lipid profile were taken. Patients were divided into two groups (100 each) based on lipid profile – Group A: normal lipid profile and Group B: abnormal lipid profile. Both groups were followed and closely observed for the development of hypertension, albuminuria, and signs and symptoms of preeclampsia. Data were collected and systematically analyzed. Results: In Group A, eight participants developed preeclampsia, whereas in Group B, 27 participants developed preeclampsia during the study period. The difference was found statistically significant (P = 0.003). Conclusion: In our study, it was observed that dyslipidemia in pregnancy is positively associated with an increased risk of preeclampsia.